Modelling Probable Distribution of Podophyllum hexandrum in North-Western Himalaya - Banerjee, Arghadyuti; Devi, Mamta; Nag, Akshay; Sharma, Ram Kumar; Kumar, Amit (Indian Forester, 2017)
Podophyllum hexandrum Royle is a critically endangered plant, which has high demand in pharmaceutical industries. In order to conserve this plant, the suitable regions of its occurrence should be known, which can be targeted for its in-situ natural plantation and phyto-diversity studies. Therefore, a niche modelling was carried out using ’Maxent’ to find out probable distribution of P. hexandrum in Himachal Pradesh (HP) of north-western Himalaya. The model output showed that 18.76 % area of HP is suitable for occurrence of P. Hexandrum. Of the total area, 7.91% constitute high and very high probability regions. The Chamba region was identified to possess largest probable area of P. hexandrum. Ecological surveys should be conducted in these regions to find out its current status for formulating plans for its conservation. The plantations of P. hexandrum, if targeted in these identified niches, would not only increase its productivity but will also maintain quality of its chemical produce. The mean temperature of the coldest quarter was observed as one of the important environmental factors responsible for its spatial distribution.